Controlling Migration: How Martha of the North and Exile Reclaim Inuit Sovereignty ([Inter]sections, 2025)
In the twenty-first century, there is increased awareness in Canada about the horrors of residential schools and the destructive actions of the government towards First Nations peoples. But this education has not extended to the histories of Arctic Indigenous peoples, whose experience of settler colonialism is different because of their geographical location. Until outside intervention, Inuit had been semi-nomadic, populating the North with small, mobile communities, as this way of life was best suited for hunting and traditional practices. Beginning in the 1950s, the Canadian government forced Inuit into centralized communities, pressuring them to leave their lands and thereby destroying a traditional way of life that had been in place for thousands of years. This article will explore the negative consequences of ‘domicide’, or the killing of one’s home, and the cultural devastation that followed. Years later, the relocation and its impacts were depicted in Inuit-made documentaries, such as Marquise Lepage’s Martha of the North in 2008, and Exile by Zacharias Kunuk in 2009. In this chapter, I will detail how Inuit-made film is helping Northerners reclaim Arctic sovereignty, documenting for future generations how their ancestors lived.